Intraoral Radiographs to Determine the Skills and Ways to Overcome Those Errors Detected by Dental Students - Jahangir Haghani; Jahangir Haghani; Sanam Mirbeigi; Hossein Safi Zadeh (Kerman University of Medical Sciences, 2013)
Background & Objective: The present study aimed to evaluate students skill in identification of intraoral radiographs faults and the way correcting them Methods: Seven intraoral radiographs included 6 periapical radiographs and 1 bitewing with common errors selected The slides were showed to each student in standard and same condition Each student must have passed the relative radiologic courses The radiographs included 7 technical errors and 4 processing errors Each student was asked to assess each film for the presence/absence of film fault(s) and to detail how to correct the faults Descriptive analytical test and ttest were used to assess the data Results: The minimum and maximum scores were 9 and 19 respectively out the total score 22 The mean score of the identification film faults was 77 and the mean score of troubleshooting the faults was 58 of 11 The ttest showed no statistically significant difference between the male and female student (P > 005) Conclusion: The skill of student in identification the film faults is superior to troubleshooting the errors There was no statistically significant difference between the male and female student